Fecundity, reproductive seasonality and maturation size of Callinectes sapidus females (Decapoda: Portunidae) in the Southeast coast of Brazil - Evandro Severino-Rodrigues; Joelson Musiello-Fernandes; Álvaro A.S. Mour; Geisa M.P. Branco; Victor O.C. Canéo (Revista de Biología Tropical, 2013)
C. sapidus fisheries has a significant influence on the economy of some countries in North America and has a relative extensive literature in these regions. However, only few papers discuss the ecology of C. sapidus in the South Atlantic, despite its economic importance in that region. We studied the fecundity, reproductive seasonality and maturation size of C. sapidus females captured in the Southeast coast of Brazil from January to December 2002. Females were separated, weighted (Wt), and cephalothorax width (CW) was measured. Furthermore, the eggs-masses were classified according to embryonic development, separated, weighted (We) and fixed. Eggs were also separated and counted, resulting in the average number of eggs per individual (Ne). A total sample of 307 females was collected: 78 young, 130 adults and 99 ovigerous. Ovigerous females showed CW between 7.49 and 15.89cm with average of 12.21cm and were distributed throughout the sample period, with highest incidence between December and March. The onset of morphological maturity (L50) occurred at CW=10.33cm, and the size in which all were mature (L100) was CW=11.20cm. Individual fecundity ranged from 689 356 to 3 438 122 with an average of 2 006 974. The CW showed a positive growth trend with Ne and We. We concluded that in order to ensure the resource sustainability, it is necessary to prohibit captures of C. sapidus in these regions, especially during summer. Additionally, our studies suggest that the minimum capture size should be 11cm of carapace width. Hay pocos estudios sobre la ecología de C. sapidus en el Atlántico Sur, a pesar de su importancia económica en la región. El presente estudio tiene como objetivo conocer la fecundidad, periodo reproductivo y talla de primera madurez morfológica de las hembras de C. sapidus, con el fin de contribuir a una mejor comprensión de la especie en el Atlántico occidental, así como ayudar en la toma de medidas de gestión en la región. Las muestras fueron recolectadas mensualmente de enero a diciembre 2002 en sudeste del Brazil. Se recogieron 307 hembras: 78 jóvenes, 130 adultos y 99 ovígeras. Las hembras ovígeras mostró su intervalo de talla de 7.49-15.89cm ancho del carapazón (AC) y se distribuyeron en todo el período de la muestra, con mayor incidencia entre diciembre y marzo. El inicio de la madurez morfológica (L50) fue con la AC=10.33cm y el tamaño que tenían todos los maduros (L100) con AC de 11.20cm. Fecundidad individual osciló entre 689 356 a 3 438 122, con una media 2 006 974. El AC mostró una tendencia positiva en el crecimiento con número de huevos y el peso del huevos. El conocimiento de los aspectos reproductivos de la población es importante en la definición de medidas de gestión para el uso sostenible con el fin de renovar y continuar con la misma.